1996
DOI: 10.1080/15216549600201012
|View full text |Cite
|
Sign up to set email alerts
|

Okadaic acid increases fibronectin synthesis in MC353‐E1 cells

Abstract: Summary: Okadaic acid, a potent specific inhibitor of serine/threonine protein phosphatases type 1 and 2A, affects several gene expressions in various cells. To determine whether okadaic acid affects the expression of fibronectin in MC3T3-E1 cells, we measured mRNA level and synthesis of fibronectin by Northern blot hybridiflation and immunoprecipitation methods, respectively. Okadaic acid (10-50 ng/ml) increased both mRNA level and synthesis of fibronectin in a dose-dependent manner. The increase of fibronect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The concentration of OKA that we used in this experiment was determined to be optimal in our previous studies [Choi et al, 1995, 1996]. Northern blot analysis of mRNAs from several normal and tumor cells indicated that OP expression was consistently stimulated by OKA treatment regardless of cellular origin.…”
Section: Resultsmentioning
confidence: 98%
“…The concentration of OKA that we used in this experiment was determined to be optimal in our previous studies [Choi et al, 1995, 1996]. Northern blot analysis of mRNAs from several normal and tumor cells indicated that OP expression was consistently stimulated by OKA treatment regardless of cellular origin.…”
Section: Resultsmentioning
confidence: 98%